Guanidine hydrochloride denaturation of dopamine‐induced α‐synuclein oligomers: A small‐angle X‐ray scattering study. Issue 1 (31st August 2013) - Pham, Chi L. L.; Kirby, Nigel; Wood, Kathleen; Ryan, Timothy; Roberts, Blaine; Sokolova, Anna; Barnham, Kevin J.; Masters, Colin L.; Knott, Robert B.; Cappai, Roberto; Curtain, Cyril C.; Rekas, Agata
ABSTRACT Alpha‐synuclein (α‐syn) forms the amyloid‐containing Lewy bodies found in the brain in Parkinson's disease. The neurotransmitter dopamine (DA) reacts with α‐syn to form SDS‐resistant soluble, non‐amyloid, and melanin‐containing oligomers. Their toxicity is debated, as is the nature of their structure and their relation to amyloid‐forming conformers of α‐syn. The small‐angle X‐ray scattering technique in combination with modeling by the ensemble optimization method showed that the un‐reacted native protein populated three broad classes of conformer, while reaction with DA gave a restricted ensemble range suggesting that the rigid melanin molecule played an important part in their structure. We found that 6 M guanidine hydrochloride did not dissociate α‐syn DA‐reacted dimers and trimers, suggesting covalent linkages. The pathological significance of covalent association is that if they are non‐toxic, the oligomers would act as a sink for toxic excess DA and α‐syn; if toxic, their stability could enhance their toxicity. We argue it is essential, therefore, to resolve the question of whether they are toxic or not. Proteins 2014; 82:10–21. © 2013 Wiley Periodicals, Inc.